Finite element modeling of high frequency irreversible electroporation - Randall, Philip (Kansas State University, 2021)
High frequency irreversible electroporation (HFIRE) is a minimally invasive, non-thermal method of soft tissue ablation that has potential to effectively treat tumors and atrial fibrillation without the severe muscular contractions that occur with monophasic pulses. The technology is relatively new, and further research is needed to understand the relationship between energy delivery parameters and effects on tissue. The objective of this study was to contribute to this understanding by using finite element method (FEM) computational models of HFIRE to determine how specific electroporation waveform parameters affect ablation patterns in tissue and validating these results against experimental measurements. The effects of heterogeneous structures on electroporation profiles were also investigated with simulations. HFIRE experiments were conducted in potato tissue, an established benchtop model for electroporation studies, with a custom generator to create rapid and easily scannable lesions using varying waveform parameters. The varied waveform parameters were voltage (1000 – 2000 V), inter-pulse delay time (2 – 10 [mu]s), pulse width (1 – 5 [mu]s), and pulse number (25 – 75). Following experiments, a flatbed scanner was used to acquire images of the visibly discolored tissue, which has been previously shown to be indicative of the ablation pattern. The experimentally observed ablation zones were then compared to model-predictions by using image processing techniques to assess the differences in area and shape. An electric field damage threshold was assigned to each given set of waveform parameters based on which value had the best fit to the model predictions. The thresholds were in the range of 200-500 V/cm for all experiments, which is in agreement with current literature. The validated computational model was then adapted to employ properties of liver tissue, and a basic blood vessel and tumor model were incorporated to analyze the effects on the electric field inside the tumor and vessel wall. The data was presented as a dose volume histogram, and the blood vessel was found to decrease the electric field inside of the tumor as the distance between them was decreased. This decrease was approximately 100 V/cm for electric field values in the tumor that were already on the verge of being below the threshold for cell death in liver tissue. Future research could build on this study by providing more empirical conductivity and lesion data for specific tissue types.
Keywords: Irreversible electroporation; HFIRE; COMSOL Multiphysics; Potato ablation; Numerical modeling; 3D printing